The Strategies to Improve Social Solidarity of Senior High School Students through History Module Based on Problems - Novita Mujiyati; Warto Warto; Leo Agung (Journal of Education and Learning (EduLearn), 2017)
This research aims to describe the strategies and the effectiveness of history module based on problems in increasing the solidarity of Senior High School Students. The efforts to improve the social solidarity of Senior High School Students were done to minimalize the problems which occurred in the school environment and to find the conflict resolution on multicultural society. To achieve the objectives, this research used combination methods of qualitative and quantitative which refer to the design of exploratory sequential mixed methods. The result of the research shows that students could understand the material and solve the problems structurally through history module based on problems. The problems arranged in the module are contemporary and associated with inter-ethnic conflict in the students’ environment while the material on the module is local history. The students’ understanding towards the material and the ability relating to the contemporary problem can improve the social solidarity. Based on the statistic data analysis, the history module based on problems is effective to improve the social society.